NCAA Division I Athletes' Engagement in Educationally Sound Activities: A Review of the Research - Eddie Comeaux; Rebecca E. Crandall (Bowling Green State University, 2019)
Today's academic support centers will have to forge a more authentically responsive approach to address the needs of intercollegiate athletes in U.S. higher education. This approach must include new and different ways of thinking about all athletes and the quality of their educational experience. This article presents findings from a review of a steadily growing body of research on the benefits of educationally sound engagement activities for Division I athletes. The review indicates that participating in purposeful engagement activities enhances athletes' personal and academic self-concept and their collective learning and communication skills. These academic-related activities for athletes are conditional on sport demands and the campus climate. The article concludes with an introduction to the Career Transition Scorecard, a data-driven approach to fostering evidence-based practices among practitioners that can improve academic engagement activities among athletes by race/ethnicity, gender, and type of sport.